Protection of National Minorities in Romania and Republic of Moldova. Guidelines - Roxana Alina Petraru (CES Working Papers, 2011)
In light of recent conflicts on the issue of minorities and European regulations, the issue of the protection of minority rights appears to be increasingly more important in a world of multiculturalism, which should be a world of dialogue and respect of human rights as well. The fundamental principles of protection of minority rights in Romania and Moldova are reflected, first, by the constitutions of both countries. In this article we analyze comparatively the two fundamental documents and we focus on the reflection of the principle of nondiscrimination based on race or ethnic origin in the national law of the two states.
Keywords: 330; minority rights; principle of nondiscrimination; international law; human rights Romania